Mechanical Abnormalities of the Airway Wall in Adult Mice After Intrauterine Growth Restriction - Noble, Peter B.; Kowlessur, Darshinee; Larcombe, Alexander N.; Donovan, Graham M.; Wang, Kimberley C. W. (Frontiers in Physiology, 2019)
Developmental abnormalities of airways may impact susceptibility to asthma in later life. We used a maternal hypoxia-induced mouse model of intrauterine growth restriction (IUGR) to examine changes in mechanical properties of the airway wall. Pregnant BALB/c mice were housed under hypoxic conditions (10.5% O2) from gestational day (GD) 11 – GD 17.5 (IUGR; term, GD 21). Following hypoxic exposure, mice were returned to a normoxic environment (21% O2). A control group of pregnant mice were housed under normoxic conditions throughout pregnancy. At 8 weeks postnatal age, offspring were euthanized and a tracheasectomy performed. Tracheal segments were studied in organ baths to measure active airway smooth muscle (ASM) stress to carbachol and assess passive mechanical properties (stiffness) from stress-strain curves. In a separate group of anaesthetised offspring, the forced oscillation technique was used to examine airway mechanics from relative changes in airway conductance during slow inflation and deflation between 0 and 20 cmH2O transrespiratory pressure. From predicted radius-pressure loops, storage and loss moduli and hysteresivity were calculated. IUGR offspring were lighter at birth (P<0.05) and remained lighter at 8 weeks of age (P<0.05) compared with Controls. Maximal stress was reduced in male IUGR offspring compared with Controls (P<0.05), but not in females. Sensitivity to contractile agonist was not affected by IUGR or sex. Compared with the Control group, airways from IUGR animals were stiffer in vitro (P<0.05). In vivo, airway hysteresivity (P<0.05) was increased in the IUGR group, but there was no difference in storage or loss moduli between groups. In summary, the effects of IUGR persist to the mature airway wall, where there are clear abnormalities to ASM contractile properties and passive wall mechanics. We propose that mechanical abnormalities of the airway wall acquired through disrupted fetal growth impact susceptibility to disease.